Characterizing near-infrared spectroscopy responses to forearm post-occlusive reactive hyperemia in healthy subjects - Bopp, Christopher M.; Townsend, Dana K.; Barstow, Thomas J. (European journal of applied physiology, 2011)
During post-occlusive reactive hyperemia (PORH) there is a temporary increase in the total hemoglobin + myoglobin (T[Hb+Mb]) signal as measured by near-infrared spectroscopy (NIRS). This transient increase predicts differences in the kinetic responses of deoxy[Hb+Mb] and oxy[Hb+Mb] during PORH. The purpose of this study was to determine whether sigmoidal (Gompertz or logistic) or exponential functions better describe these response curves during PORH. The fit of the three functions (exponential, Gompertz and logistic) to the NIRS responses, as determined from residual sum of squares, was compared using repeated measures ANOVA on Ranks. The Gompertz function provided a better fit to the oxy[Hb+Mb] response curve than did either the exponential or logistic function ( χ 2 = 21.7, df = 2, p < 0.001). The logistic function provided a better fit for the deoxy[Hb+Mb] response ( χ 2 = 22.9, df = 2, p < 0.001) than did either the Gompertz or exponential functions. For both NIRS signals, the better fitting sigmoidal functions fit the data well, with an average r value of 0.99 or greater. Adipose tissue thickness was correlated with parameters related to signal strength (amplitude, r = 0.86–0.89; baseline, r = 0.67–0.75; all p < 0.001) but was not related to kinetic parameters (time constant and inflection point; p > 0.05 for all comparisons). These results suggest that during PORH distinct sigmoidal mathematical functions best describe the responses of the oxy[Hb+Mb] (Gompertz) and deoxy[Hb+Mb] (logistic) as measured by NIRS. Further, differences in both the kinetic and amplitude aspects for the responses of oxy[Hb+Mb] and deoxy[Hb+Mb] predict the observed transient change in T[Hb+Mb]. Our methods provide a technique to evaluate and quantify NIRS responses during PORH, which may have clinical utility.